3D Time-Domain Airborne EM Inversion with Finite-Volume Method. Issue 1 (1st December 2018) - Ren, Xiuyan; Macnae, James; Yin, Changchun; Liu, Yunhe; Zhang, Bo
Abstract : We investigate an algorithm for 3D time-domain AEM inversion with the finite-volume and direct Gauss-Newton methods. We separate a spatially varying secondary field from the 1D background in time-domain, and constrain the calculation to be within the small volume of influence of airborne EM secondary source, resulting in more compact discretization. To demonstrate the validity and merits of 3D inversion, we first compare the results with 1D inversion on synthetic data for a horizontal conductor and a dipping plate, which shows that both methods can well recover the horizontal conductor, while only 3D inversion can offer good recovery for the dipping plate. We apply our 3D algorithm to invert GEOTEM data obtained over the Lisheen deposit in Ireland to map the sulphides at depth and obtain similar results to 1D inversion but with better data fitting, further showing the effectiveness of our 3D inversion algorithm.